Influenza A (H1N1) outbreak in the Asokore Mampong Sub – Municipal, Ghana: A case report - Justice Ofori-Amoah; Reindolf Anokye; Alfred Mensah; Francisca Ahiavih Esinam; John Baffoe Yeboah; Isaac Kofi Kontor (Cogent Medicine, 2019)
Swine Flu or Influenza A (H1N1) is caused by one of several swine influenza A strains and its highly contagious. The transmission of the virus is from person-to-person and is similar to how seasonal influenza spreads. This report describes an Influenza A Virus (H1N1) outbreak in Asokore Mampong Sub-Municipal. Ninety-six (96) people were infected by the Influenza A (H1N1), and four (4) of them died. Those who died were lodging at the Sadler house; Jubilee House and Yaa Achiaa House. Three (3) health staff at KNUST hospital emergency unit were also infected, but they were treated and discharged. Three (3) of those who died as a result of the outbreak were males. An outbreak of H1N1 influenza type A caused by the H1N1 pdm09 virus on the campus of Kumasi Academy (KUMACA) led to Ninety-six (96) people becoming infected and four (4) dying. Several steps were taken by a national and regional multi-sectoral team from the World Health Organization, Ghana Health Service HQ as well as the Regional Health Directorate to manage the situation. Health education on H1NI must be intensified and sustained in the municipality as well as disease surveillance.